The low diverse gastric microbiome of the jellyfish Cotylorhiza tuberculata is dominated by four novel taxa. (11th May 2017) - Viver, Tomeu; Orellana, Luis H.; Hatt, Janet K.; Urdiain, Mercedes; Díaz, Sara; Richter, Michael; Antón, Josefa; Avian, Massimo; Amann, Rudolf; Konstantinidis, Konstantinos T.; Rosselló‐Móra, Ramon
Summary: Cotylorhiza tuberculata is an important scyphozoan jellyfish producing population blooms in the Mediterranean probably due to pelagic ecosystem's decay. Its gastric cavity can serve as a simple model of microbial–animal digestive associations, yet poorly characterized. Using state‐of‐the‐art metagenomic population binning and catalyzed reporter deposition fluorescence in situ hybridization (CARD‐FISH), we show that only four novel clonal phylotypes were consistently associated with multiple jellyfish adults. Two affiliated close to Spiroplasma and Mycoplasma genera, one to chlamydial ' Candidatus Syngnamydia', and one to bacteroidetal Tenacibaculum, and were at least one order of magnitude more abundant than any other bacteria detected. Metabolic modelling predicted an aerobic heterotrophic lifestyle for the chlamydia, which were found intracellularly in Onychodromopsis ‐like ciliates. The Spiroplasma ‐like organism was predicted to be an anaerobic fermenter associated to some jellyfish cells, whereas the Tenacibaculum ‐like as free‐living aerobic heterotroph, densely colonizing the mesogleal axis inside the gastric filaments. The association between the jellyfish and its reduced microbiome was close and temporally stable, and possibly related to food digestion and protection from pathogens. Based on the genomic and microscopic data, we propose three candidate taxa: ' Candidatus Syngnamydia medusae', ' Candidatus Medusoplasma mediterranei' and ' Candidatus Tenacibaculum medusae'.